Analisis Identifikasi Sektor Perekonomian Sebagai Sektor Basis dan Sektor Potensial di Kota Bogor - Resista Vikaliana (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
This study aims to determine the sectors that become the basis sector and non-base in the city of Bogor, then to know the performance of each sector in the city of Bogor, and to know the sector that became a potential sector in the city of Bogor. The research was conducted by using Location Quotient / LQ method. In the city of Bogor, from the period of 2011 to 2015 there is one sector of the highest base of electricity and gas procurement sector. Of the 16 economic sectors, the economic sector including the basic sector in 2011 is the procurement of electricity and gas, the transportation and warehousing sectors, the financial services sector and insurance and other services sectors. In addition to these four sectors in 2011, in 2012-2015, it increased by 7 sectors, to 11. The additional sectors were water supply, waste management, waste, construction, and large and retail trade sectors; car and motorcycle repair, accommodation, food and beverage sector, information and communications sector, corporate services sector, health services sector and social activities. then that included in the non-base sector is the other five sectors.In the city of Bogor the performance of the economic sector can be explained that the sector that has the average value of Regional Growth (PR) is the highest sector of procurement of electricity and gas. This value indicates that the growth of electricity and gas procurement sector in Bogor City is higher than that of Indonesia. In Bogor City from 2011 to 2015 included in the potential sector is sector. Then from these sectors, the most potential sector or the most potential sector is the electricity and gas procurement sector.From the results of research that has been obtained by researchers, the researchers provide suggestions that must be taken are as follows: First, the base sector should be more maintained and developed again without exclude development against other sectors. The electricity and gas procurement sector that contributes to the GRDP should be developed by industrializing in cooperation with investors, so that the contribution from the gas and electricity procurement sector can increase again. Second, planning in development should be given to sectors that have the potential to be developed as a top priority so that development can be carried out more optimally.